2019
DOI: 10.1093/jac/dkz225
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive transferrin to reduce the emergence of antibiotic resistance in Gram-negative bacteria

Abstract: Background New strategies are needed to slow the emergence of antibiotic resistance among bacterial pathogens. In particular, society is experiencing a crisis of antibiotic-resistant infections caused by Gram-negative bacterial pathogens and novel therapeutics are desperately needed to combat such diseases. Acquisition of iron from the host is a nearly universal requirement for microbial pathogens—including Gram-negative bacteria—to cause infection. We have previously reported that apo-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Both compounds can inhibit the formation of biofilms in P. aeruginosa [ 58 , 59 , 60 ]. Their in vitro activity against S. aureus , A. baumannii , K. pneumoniae and C. albicans has also been described [ 61 , 62 ]. However, some pathogens, such as P. aeruginosa , are able to use these proteins as an iron source [ 63 ], which limits their efficacy as antimicrobials against these microorganisms.…”
Section: Iron Chelators As Antimicrobial Agentsmentioning
confidence: 99%
“…Both compounds can inhibit the formation of biofilms in P. aeruginosa [ 58 , 59 , 60 ]. Their in vitro activity against S. aureus , A. baumannii , K. pneumoniae and C. albicans has also been described [ 61 , 62 ]. However, some pathogens, such as P. aeruginosa , are able to use these proteins as an iron source [ 63 ], which limits their efficacy as antimicrobials against these microorganisms.…”
Section: Iron Chelators As Antimicrobial Agentsmentioning
confidence: 99%
“…The results showed that DMC has the ability to prevent MRSA from growth and suggested the potential of DMC to be further studied as an antibacterial agent. The kill kinetics of antimicrobial activity provides more accurate description of antimicrobial agents, in contrast to the MIC assay [34]. Based on FICI, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The kill kinetics of antimicrobial activity provides a more accurate description of antimicrobial agents, in contrast to the MIC assay [ 57 ]. In order to determine the synergistic effect from the survival curve of bacteria, the standard strain ATCC 33591 and clinical strain DPS-2 were used to conduct experiments, and three treatment modes (DMC alone, GEN alone and GEN combined with DMC) were designed to compare the antibacterial effects with the control (no drug).…”
Section: Methodsmentioning
confidence: 99%